EFL STUDENTSâ AWARENESS AND ATTITUDES ON ENVIRONMENTAL ISSUES AND ITS EDUCATIONAL SOLUTION - Fauzan, Akhmad (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2013)
The purpose of this paper is to illustrate the attitudes and awareness of secondary school students in Central Kalimantan towards environmental issues and to propose a framework to raise or improve those attitudes and awareness. The environmental issues covered in this paper are related to forest, bush, and peat land fires. The paper elaborates the secondary school studentsâ attitudes and awareness obtained from questionnaires which were distributed to 12 Regencies and 1 City in Central Kalimantan. The findings in this paper show that most of the samples of secondary school students have insufficient knowledge about environmental issues and how to overcome the problems. Most of them did not take any action to prevent environmental destruction though they have expectation that their surroundings will be better in the future. Based on the findings, there are practical implications in attempts to minimize the problems which are happening annually in relation to the environment, particularly, peat land fires. There should be learning materials at school that can add to the knowledge of the students towards environment conservation. Schools have a major role to play because students are bound to follow formal education thus it fills the gap between studentsâ knowledge and environmental problems.Keywords: attitude, awareness, environmental issues, English learning materials